The Role of Social Systems in Absorption of Immigrants in Israel - Tamir, Vered; Ein-Tal, Irit (International Journal of Criminology and Sociology, 2024)
Immigrants from the Former Soviet Union (FSU) are the largest ethnic unit to have arrived in Israel and, as such, have had a major impact on Israeli society in cultural, social and demographic terms. The manner in which the immigrants were absorbed in social institutions influenced the adaptation strategies they adopted, which changed over time. The research is aimed at examining the extent to which the immigrants have, according to their perception, adapted to the social frameworks, based on their experiences in connecting with the local population through the educational system and the Israel Defense Forces (IDF). The research is a qualitative one, in the framework of which interviews were conducted with 28 immigrants who had immigrated to Israel as children and adolescents. The immigrants developed adaptation strategies which changed as they transitioned from the educational system to the military framework, and subsequently settled into civilian life.